Penerapan Layanan Sistem Informasi di PT Jasindo Kota Jambi - Safrudin Simatupang (Journal on Education, 2023)
Information is increasingly realized that it has become a resource that needs to be managed very well. This is due to increasingly complex business and organizational activities. In addition, the ability to understand computers must be better and be able to provide convenience to users to make information processing easier, faster and more precise. Understanding information for an organization must be complex, especially regarding understanding a system within an agency. Such as the management of the insurance service development information system at PT Jasindo (Persero) Jambi City. The information system at PT Jasindo (Persero) Jambi Branch Office has used a computerized method that is structured in such a way as to produce good and relevant data so that there are no errors between the decision maker and the system used.